Iodine-doped ZnO nanopillar arrays for perovskite solar cells with high efficiency up to 18.24%. Issue 24 (1st June 2017) - Zheng, Yan-Zhen; Zhao, Er-Fei; Meng, Fan-Li; Lai, Xue-Sen; Dong, Xue-Mei; Wu, Jiao-Jiao; Tao, Xia
Abstract : A compact and even ZnO:I nanopillar planar electron transport layer (ETL) is prepared to enable deposition of a fully covering and highly uniform perovskite layer by a facile one-step spin-coating process method. Such a ZnO:I nanopillar ETL film exhibits high optical transparency, favorable work function and superior electron extraction ability, leading to the opt-electrical conversion efficiency as high as 18.24%. Abstract : Fabricating a 1D electron transport layer (ETL) with bifunctionalities capable of effectively extracting electrons from a fully covering perovskite layer and synergistically blocking charge recombination between electrons in the cathode and holes in the perovskite is of great importance for high performance perovskite solar cells (PSCs). Herein, we report a compact and even ZnO:I nanopillar planar ETL that enables the deposition of a fully covering and highly uniform perovskite layer by a facile one-step spin-coating method. We find that the crystal growth of 1D ZnO along the [0001] direction of a hexagonal single crystal is largely suppressed owing to iodine doping, which leads to a low-aspect-ratio and dense 1D nanopillar aligned architecture, and thus promotes one-step deposition of the perovskite layer. As characterized by optical spectroscopy, Kelvin probe force microscopy, and electrochemical assays, the resultant ZnO:I nanopillar ETL film exhibits high optical transparency, a reduced work function and superior electron extraction ability. As a result, the optical–electrical conversion efficiency is promoted to as high as 18.24%, exceeding the previous highest efficiency recorded for 1D ETL based CH3 NH3 PbI3 PSCs. The enhanced performance is discussed in detail based on a well-matched work function between ZnO:I and the perovskite, fast electron extraction from the perovskite into the ZnO:I ETL, and improved electron transport rate and retarded charge recombination at the 1D ZnO:I ETL/perovskite interface. This work provides a novel and efficient 1D ETL via alien element doping and crystal oriented growth control for maximizing PSC performance.